Mengenali Bagian-Bagian Komputer Melalui Teknologi Augmented Reality - Syallomita Pompayo; Melky Pangemanan; Augustinus Robin Butarbutar (Jurnal Praba : Jurnal Rumpun Kesehatan Umum, 2024)
Learning about computer components in schools often relies on textbooks or practical exercises, which can sometimes result in student boredom. Therefore, learning requires innovation to optimize the student learning experience and provide a fresh perspective on the material. One such innovative approach is the use of augmented reality (AR) technology. AR is a breakthrough and innovation in the fields of multimedia and image processing that is rapidly evolving. This technology can transform a previously flat or two-dimensional object into something that appears real and integrated with the surrounding environment. Consequently, it can be applied in education to provide an engaging and enjoyable visual experience. This research aims to develop an educational application for introducing computer components using augmented reality technology, which is expected to assist teachers in delivering the material effectively to students. The research employs a Research and Development methodology, with application testing conducted using Alpha testing. The result of this study is an educational media application for learning about computer components using augmented reality technology, which is engaging and adds a new dimension to the teaching and learning process.